Land Acquisition Regarding Agency Land: Construction Of The Bawen-Jogja Toll Road On SMKN 1 Bawen Agricultural Land - Anjhany, Lintar (Semarang State University Undergraduate Law and Society Review, 2025)
The construction of the Bawen-Jogja Toll Road has caused problems in the acquisition of agricultural land of SMK Negeri 1 Bawen covering an area of 1,752 m2, which is constrained by land ownership status. The complicated administrative process slows down the settlement of compensation. The purpose of this article is to analyze the land acquisition process and its compliance with Law Number 2 of 2012 Regarding Land Acquisition for Public Interest. The research method uses a normative legal approach with analysis of laws and regulations, interviews, and document studies. The results of the study show weaknesses in transparency and stakeholder involvement in the land acquisition process. Problematic land ownership status hinders compensation negotiations. In conclusion, the land acquisition process is not optimal and requires system improvements to ensure legal compliance, efficiency, and fairness. Improvements in procedures and transparency are urgently needed to prevent similar obstacles in future infrastructure projects.